6.0k views
0 votes
Find f(–2) for f(x) = 2 • 3x.

User CCCC
by
5.6k points

2 Answers

3 votes

Answer:

f(-2)=-12

Explanation:

This question asks us to find f(-2). This means we need to find out what f(x), or y is, when x is equal to -2.

f(x)=2*3x

Therefore, we can substitute -2 in for every x.

f(-2)=2*3(-2)

Solve according to PEMDAS (Parentheses, Exponents, Multiplication, Division , Addition, Subtraction)

Multiply 3 and -2 first

f(-2)=2*-6

Multiply 2 and -6

f(-2)= -12

User Genio
by
5.2k points
2 votes

Answer:

f(-2) = -12

Explanation:

f(x) = 2 • 3x.

Let x = -2

f(-2) = 2* 3(-2)

= -12

User Volcanic
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.